Phenolic Compounds from Clinopodium chinense (Benth.) O. Kuntze and Their Inhibitory Effects on α‐Glucosidase and Vascular Endothelial Cells Injury. Issue 5 (May 2016) - Zeng, Biao; Chen, Kai; Du, Ping; Wang, Shan‐Shan; Ren, Bei; Ren, Yan‐Li; Yan, Hang‐Song; Liang, Yan; Wu, Fei‐Hua
Abstract : Following an in vitro bioactivity‐guided fractionation procedure, 14 compounds including eight flavonoids and six phenylpropanoids were isolated and identified from the AcOEt fraction of Clinopodium chinense (Benth .) O. Kuntze . All constituents were tested for α ‐glucosidase and high glucose‐induced injury in human umbilical vein endothelial cells (HUVECs) inhibitory activities. All constituents exhibited varying degrees α ‐glucosidase inhibitory activity and protective activity on HUVECs. Among them, luteolin (2 ), eriodictyol (5 ), ethyl rosmarinate (13 ), and clinopodic acids B (14 ) were proved to be potent α ‐glucosidase inhibitors with IC 50 value ranging from 0.6 to 2.0 μm . Additionally, luteolin (2 ), naringenin (4 ), eriodictyol (5 ), ethyl (2 R )‐3‐(3, 4‐dihydroxyphenyl)‐2‐hydroxypropanate (9 ), caffeic acid (11 ), ethyl rosmarinate (13 ), and clinopodic acids B (14 ) significantly ameliorate HUVECs injury induced by high glucose with an approximate EC 50 value of 3 – 36 μm . These results suggest that the 14 bioactive constituents were responsible for hypoglycemic and protective vascular endothelium effect of C. chinense (Benth .) O. Kuntze and their structure–activity relationship was also analyzed briefly. Eriodictyol, luteolin, ethyl rosmarinate, and clinopodic acids B were the potential lead compounds of antidiabetic drugs. Abstract :